Equity of Carbon Pricing Policies in Mitigating Climate Change: A Comparative Study of Different Policy Designs - Chhoub Kesor (Journal of Public Representative and Society Provision, 2022)
Carbon pricing policies are investigated for their efficacy and fairness in reducing greenhouse gas emissions in Asian nations. Through an examination of various policy frameworks, we conclude that carbon pricing policies are the most promising for lowering global warming pollution. However, the distributional effects of these policies on family income are not uniform. We find that rebates or investment in renewable energy are effective revenue recycling methods for reducing the regressive impact of carbon pricing policies on low-income households. In addition, it may be easier to reach climate targets if policy designs put an emphasis on lowering emissions rather than increasing income. These results indicate that carbon pricing policies may play a significant role in reducing the effects of global warming, but that they must be designed with equity considerations in mind to be both successful and fair. Policymakers can benefit from more information about the design and implementation of carbon pricing policies across sectors, income groups, and regions in order to successfully mitigate climate change while assuring their equity.